Singing of devotional abhangas - Mumbai Archive Project Team (Jio Institute, 2024)
Devotional abhangas are sung as part of the all-night vigil. Abhangas are typically written in quatrains (four-line stanzas) with a simple and rhythmic structure set to melodious tunes, making them easy to sing and remember. They are accompanied by traditional instruments such as the dhol, the kartal, the manjeera, and the tanpura.